Ventaja comparativa revelada del sector apícola de México en el comercio internacional de miel, periodo 2000-2016 - Olvera García, José David (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
In the present research work, it is "revealed" the comparative advantage of the apicultural sector of Mexico, within the agricultural sector worldwide, through the international trade of honey, during the period 2000-2016. To achieve this, the comparative advantage (or comparative disadvantage) of all honey exporting countries was measured over the period 2000-2016. This measurement was carried out through five different indexes of Revealed Comparative Advantage (RCA), proposed by the following authors: The Hungarian economist Bela Balassa, in the year 1965; the Japanese Hisao Kanamori, in 1977; the American Thomas L. Vollrath, in 1991; the Slovakian Stefan Bojnec, in 2001; and the Hawaiian Economists Run Yu, Junning Cai and PingSun Leung, in 2008. Regarding the results obtained with the RCA indexes, the Balassa (1965) and Kanamori (1977) indexes showed identical values, "revealing" 32 countries with a comparative advantage in the export of honey, within the agricultural sector. Likewise, they showed identical values, but in a different range, the indices of Vollrath (1991) and Bojnec (2001), "revealing" 66 countries with a comparative advantage in the international honey trade, within the agricultural sector. For its part, the index of Yu, Cai & Leung (2008), "revealed" 32 countries with comparative advantage, which were "revealed" by the Balassa and Kanamori indexes, but in different order and scores. To explain the comparative advantage of countries in international honey trade, instead of applying the Ricardian concept, the definition of comparative advantage is used based on the neoclassical theory of economics, which is based, to a greater extent, on the factor endowment of the countries and, to a lesser extent, the difference in the tastes and preferences of the consumers in the different countries.

En el presente trabajo de investigación, se “revela” la ventaja comparativa del sector apícola de México y de los demás países exportadores, a nivel mundial y dentro del sector agropecuario, a través del comercio internacional de miel, durante el periodo 2000-2016. Para lograr lo anterior, se realizó la medición de la ventaja comparativa (o desventaja comparativa) de todos los países exportadores de miel, a lo largo del periodo 2000-2016. Dicha medición, se llevó a cabo mediante cinco diferentes índices de Ventaja Comparativa Revelada (VCR), propuestos por los siguientes autores: el economista húngaro Bela Balassa, en el año 1965; el japonés Hisao Kanamori, en 1977; el estadounidense Thomas L. Vollrath, en 1991; el eslovaco Stefan Bojnec, en 2001; y los economistas hawaianos Run Yu, Junning Cai y PingSun Leung, en el año 2008. Respecto a los resultados obtenidos con los índices de VCR, los índices de Balassa (1965) y de Kanamori (1977), mostraron valores idénticos, “revelando” a 32 países con ventaja comparativa en la exportación de miel, dentro del sector agropecuario. Así mismo, mostraron valores idénticos, pero en distinto rango, los índices de Vollrath (1991) y de Bojnec (2001), “revelando” a 66 países con ventaja comparativa en el comercio internacional de miel, dentro del sector agropecuario. Por su parte, el índice de Yu, Cai & Leung (2008), “reveló” a 32 países con ventaja comparativa, mismos que fueron “revelados” por los índices de Balassa y de Kanamori, pero en distinto orden y puntajes. Para identificar la ventaja comparativa de los países en el comercio internacional de miel, en lugar de aplicar el concepto ricardiano, se utiliza la definición de ventaja comparativa con base en la teoría neoclásica de la economía, la cual se basa, en mayor medida, en la dotación de factores de los países y, en menor medida, en la diferencia de los gustos y preferencias de los consumidores en los diversos países.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Negocios Internacionales
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2018-1856; Consumo nacional per cápita; Apicultura; Teoría neoclásica; Ventaja comparativa; VCR; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1081